Abandono familiar y su influencia en el estado emocional de una mujer de 65 años internada en el Centro Residencial Gerontológico Atalaya del cantón Chillanes provincia de Bolívar - Velasco Gaibor, Carmen Elisa (2022)
As the human being ages, multiple changes are generated at the biological, physical, psychological, cognitive, social and family levels, these changes require in the elderly adult preparation, training, acceptance and adaptation, which is also important for the members of the environment. On the other hand, the physical changes are easy to identify, but the same does not happen with the changes that arise in the emotional state. For this reason, the objective of this research focuses on analyzing whether family abandonment influences the emotional state of a 65-year-old woman admitted to a gerontological residential center. In the collection of information, an extensive bibliographic research was carried out and a practical case was worked, where the intervention was carried out and a diagnosis was obtained. Based on this, a therapeutic scheme focused on cognitive behavioral therapy by the psychologist Aaron Beck is proposed. In addition, research methods such as case study, psychometric method and clinical method were used. The techniques used are psychological interview, medical history, direct observation, the Beck depression inventory and the Yesavage geriatric depression scale. Consequently, the results indicate that family abandonment, the situation of Covid-19 and being in an asylum directly influence the symptoms that the patient presents, personal, social, physical and mental health have also been affected. In conclusion, family abandonment has a direct impact on the deterioration of the emotional state of the adult who is hospitalized.